Building an Inclusive and Sustainable Smart City: A Pilot Project on Decentralized Digital Identity and Data Governance in Santa Rosa - Castanho, Carla O.; Chequin, Marcelo P.; M. Neto, Fernando; Vargas, Paulo C.; Sawicki, Sandro; Frantz, Rafael Z. (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
This paper presents the initiative to transform the municipality of Santa Rosa into an intelligent and sustainable region. The project is fundamentally guided by the principles of Equality, Diversity, and Inclusion. For its implementation, a smart city pilot lab was built to validate technologies in a real-world environment. The study focuses on exploring decentralized solutions that enable citizens to securely access urban data through digital identification. The experimental evaluation of access control utilizes the concept of Decentralized Digital Identity, supported by Hyperledger Indy and Trustchain technologies. This research aims to advance the debate on the integration of decentralized identity into smart city infrastructure.